2008
DOI: 10.1038/jp.2008.138
|View full text |Cite
|
Sign up to set email alerts
|

Ascertaining causes of neonatal deaths using verbal autopsy: current methods and challenges

Abstract: Objective: 'Verbal autopsy' (VA) is used to ascertain cause of death in countries where vital registration systems are lacking. Current VA methods for neonatal deaths vary widely and suffer from several limitations. We aimed to: (1) review current neonatal VA methods, (2) identify gaps and limitations, (3) illustrate some limitations using VA data and (4) identify new approaches in methodology and analysis.Study Design: Rolling techniques and database search terms were used to identify articles that described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 37 publications
(88 reference statements)
2
39
1
Order By: Relevance
“…We interviewed mothers within two weeks of a death, and it is conceivable that the mothers’ grief may have precluded accurate responses to VA. This possibility has not been borne out in other VA studies, where recall bias has been noted to sometimes occur if mothers are interviewed one year or later than the death 14, 21, 38 . There is also no validation component of this study per se with the use of laboratory, radiologic or microbiologic investigations; however, VA has been widely used and subjected to rigorous investigation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We interviewed mothers within two weeks of a death, and it is conceivable that the mothers’ grief may have precluded accurate responses to VA. This possibility has not been borne out in other VA studies, where recall bias has been noted to sometimes occur if mothers are interviewed one year or later than the death 14, 21, 38 . There is also no validation component of this study per se with the use of laboratory, radiologic or microbiologic investigations; however, VA has been widely used and subjected to rigorous investigation.…”
Section: Discussionmentioning
confidence: 93%
“…Complex statistical models are not a panacea and cannot replace the sensitivity of counting births and deaths. As the shift continues from global and regional estimates of COD to national and sub-national estimates for monitoring progress towards MDG4 and providing evidence for backing national policies, increasing numbers of VA validation studies to ascertain cause of SB and neonatal death are emerging in the literature 13, 1517, 21 . The findings from these studies have generally been favorable and VA has been found to reliably identify several of the most common causes of neonatal illness and death, although generalizability is limited by the differences in methods and procedures used in different settings.…”
Section: Discussionmentioning
confidence: 99%
“…VA is a useful tool for establishing the probable cause of death (COD) by interviewing a caregiver or a close person who witnessed the death event [1]. The usefulness of the VA tool for filling the information gap on causes of death in low and middle income countries has been discussed extensively [710]. In the present study, we describe the main causes of death in the Kombewa HDSS, in rural Western Kenya, in the years 2011–2015.…”
Section: Introductionmentioning
confidence: 99%
“…Verbal autopsy methods (questionnaires used with family members after the death) are the only option for causeof-death data for the majority of neonatal deaths and stillbirths [28]. There have been advances in case definitions and algorithms for use in verbal autopsy, but full consensus and consistent use is still lacking, particularly for hierarchical attribution if the baby died with signs suggestive of several possible causes-of-death [29][30][31][32][33][34][35][36].…”
Section: Lack Of Comparable Cause-specific Datamentioning
confidence: 99%